Pengembangan Keterampilan Menjelaskan pada Anak Usia Dini melalui Pendekatan Pembelajaran Interaktif - Nur Jadidah; Kholidah Nur; Ummi Kalsum (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to examine the effectiveness of interactive learning approaches in developing explanation skills in early childhood. Explanation skills are an important aspect in children's language, cognitive, and communication development, which supports critical thinking skills and effective social relationships. Although important, these skills are still relatively low in early childhood in Indonesia, largely due to less supportive learning methods. Interactive learning approaches involving games, stories, and discussions have been identified as a solution to improve these skills. This study used a quasi-experimental design with two groups of subjects, namely the experimental group given interactive learning interventions and the control group using conventional methods. Data were analyzed using a t-test to compare the pretest and posttest results between the two groups. The results showed that the interactive learning approach significantly improved early childhood skills. This study suggests the need for ongoing training for teachers and collaboration between schools and families to support the implementation of more effective and relevant learning. These findings are expected to contribute to the development of innovative learning strategies in early childhood education.